Concurrent Validity of the Cognitive Assessment of Minnesota in Older Adults with and without Depressive Symptoms - Leilani Feliciano; Jonathan C. Baker; Sarah L. Anderson; Linda A. LeBlanc; David M. Orchanian (Journal of Aging Research)
Cognitive impairment represents a common mental health problem in community-dwelling and institutionalized older adults, and the prevalence increases with age. Multidisciplinary teams are often asked to assess cognitive and functional impairment in this population. The Cognitive Assessment of Minnesota was created by occupational therapists for this purpose and is frequently used, but has not been extensively validated. This study examined the performance of the CAM and compared it to the MMSE with 113 outpatient clinic patients over the age of 60. Subgroups were established based on scores on a depression inventory to determine if the presence of depressed mood altered the relationship between the measures. Both measures demonstrated good internal consistency. The overall correlation between the two measures was high, statistically significant and remained high regardless of depression status. We offer recommendations about the utility of each measure in screening cognitive functioning for older adults.